Clinical performance of nanofilled and microhybrid direct composite restorations on endodontically treated teeth - Toz Akalın, Tuğba; Öztürk Bozkurt, Funda; Kara Tuncer, Aysun; Gözükara Bağ, Harika; Özcan, Mutlu (Dennis Barber Ltd, 2019)
This study evaluated the clinical performance of direct restorations made of nanofilled and microhybrid resin composites in endodontically treated teeth. Twenty patients (11 males, 9 females; mean age: 34.2 +/- 10) that met the inclusion criteria received a total of 48 restorations. After employing etch-and-rinse adhesive system, one dentist placed all restorations using either a nanofilled (Filtek Ultimate) or microhybrid (Filtek Z250) resin composite. The restorations were clinically reviewed at baseline, 6 months, and up to 2 years using the modified United States Public Health Service (USPHS) criteria. The changes were analyzed using the McNemar test and marginal homogeneity tests (p< 0.05). The mean observation period was 17.4 months. With respect to color match, marginal adaptation, secondary caries, and surface texture, no significant differences were found between the two restorative materials (p> 0.05). Most restorations yielded alpha or bravo scores with respect to the evaluation criteria. Five restorations failed due to chipping up to 2 years (1 microhybrid at 6 m, and 3 at 2 years; 1 nanofilled at 2 y) and were repaired. One complete replacement and one extraction due to endodontic complications were needed for 2 microhybrid resin group at 2 years.
WOS: 000459372800006
PubMed ID: 30779495
Keywords: Adhesion; Aging; Clinical Trial; Esthetics; Endodontics; Resin Composite; USPHS; Aged Restorations; Endodontically Treated Tooth